CONTENT OF PREPARING FUTURE TEACHERS FOR PROFESSIONAL INNOVATIVE ACTIVITY (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article discusses the content of training future teachers for professional innovative activities, its main directions, its importance in the modern educational process and effective methods. The issues of combining theoretical knowledge and practical skills in training for professional innovative activities, the introduction of innovative technologies, the formation and continuous development of the teacher's professional competence are analyzed. The article also shows ways to increase the effectiveness of education based on pedagogical practice, modern methods and international experience in training for innovative activities.v